Acute coronary syndrome : multidisciplinary and pathway-based approach - Arshad, Aysha (Springer, 2008)
Acute coronary syndrome (ACS) affects millions of patients annually and requires immediate diagnosis and therapy. In addition, with the aging of the global population, ACS will become an even greater medical emergency, not only for the emergency room and cardiology physicians, but for all other specialists having to treat an older population at risk of ACS. Acute Coronary Syndrome provides practical approaches for optimal therapy of patients with acute coronary syndrome and will become the handbook of choice for all trainees and non-medical specialists looking for an algorithm-based triage and prompt treatment of their patients with ACS.